2009
DOI: 10.1007/s11103-009-9456-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Brachypodium genome and its syntenic relationship with rice and wheat

Abstract: Brachypodium distachyon (Brachypodium) has been recently recognized as an emerging model system for both comparative and functional genomics in grass species. In this study, 55,221 repeat masked Brachypodium BAC end sequences (BES) were used for comparative analysis against the 12 rice pseudomolecules. The analysis revealed that *26.4% of BES have significant matches with the rice genome and 82.4% of the matches were homologous to known genes. Further analysis of paired-end BES and *1.0 Mb sequences from nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 70 publications
5
44
1
1
Order By: Relevance
“…Gene islands reflect inhomogeneous expansion of the genome and are not found in compact genome species such as rice, Arabidopsis thaliana (Arabidopsis Genome Initiative, 2000), and Brachypodium (Huo et al, 2009). They are, however, common features of large and repetitive genomes, such as the 2.5 Gb maize genome.…”
Section: Genes Are Mainly Clustered Into Small Islands Spread Out Alomentioning
confidence: 99%
“…Gene islands reflect inhomogeneous expansion of the genome and are not found in compact genome species such as rice, Arabidopsis thaliana (Arabidopsis Genome Initiative, 2000), and Brachypodium (Huo et al, 2009). They are, however, common features of large and repetitive genomes, such as the 2.5 Gb maize genome.…”
Section: Genes Are Mainly Clustered Into Small Islands Spread Out Alomentioning
confidence: 99%
“…Various molecular phylogenetic analyses have shown that Brachypodium diverged from the ancestral stock of Pooideae immediately prior to the radiation of the modern ''core pooids'' (Catalan et al 1997;Catalan and Olmstead 2000;Draper et al 2001). It is also ancestral, but equally related to, Avena and Triticum (Kellogg 2001;Huo et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In both plant species, larger rust infection sites were proven to be able to suppress callose production in weak or old cells, supporting the theory of the presence of mechanistic overlap between the Brachypodium response to cereal rust infection and the wheat basal defence response. The data also shows the absence of change in salicylic acid level in Brachypodium leaf upon artificial infection with Puccinia subtypes [16][17][18].…”
Section: Main Partmentioning
confidence: 99%